Changes In The National Life Cycle In Modern Society: Causes and Consequences - Boymurodov Zohid Shokirovich (Indonesian Journal Publisher, 2025)
This study philosophically analyzes the causes and consequences of the evolving national lifestyle in modern Uzbek society. It aims to examine how liberalization of the economy, pragmatic transformation of public policy, social openness, and the emergence of a new spiritual space have reshaped youth behavior, social roles, and national identity. The research applies a theoretical and analytical method based on scientific literature and observations of societal changes. Results indicate that these transformations have positively influenced young people’s rapid adaptation to market economy realities, increased entrepreneurial activity, and strengthened mutual assistance values. However, challenges persist, including extended adolescence, the prioritization of formal education over true learning, labor market mismatches, rising youth migration, and shifting family dynamics. The findings highlight the urgent need for systematic solutions to ensure the sustainable development of youth lifestyles while balancing tradition and modernization.